Obstacles to Entrepreneurship in Pakistan - Alam, Noor; Shopovski, Jovan; El Alaoui, Aicha; Kvirkvaia, Murtaz; Uche Ofili, Onyeka (European Scientific Journal, ESJ, 2023)
In Pakistan, the government’s much greater patronising of investment at a large industrial level with the belief that it had been promoting entrepreneurship was the result of the connivance/collusion between civil servants and business tycoons, who created a new definition of entrepreneurship that was contrary to the norms of the established theories. The Paper-II is a continuation of our previous paper on the same topic (see Alaoui et al. [2016]) however with an approach of intertemporal analysis and focusing Pakistan which includes population from SMEs and non-SMEs. The fundamental conclusion of this study is that there is no one factor that prevents the growth and expansion of SMEs in Pakistan, but political instability, a deficient legal system, red tape-filled bureaucracy, and bank loans and grants do so to some extent. It has been discovered that intertemporal factors significantly affect how respondents behave. The study notices that one of the main barriers to the growth of SMEs in Pakistan is connivance/collusion between public policy makers and business tycoons, and that the myth that government is patronising investment at large industrial level with the belief of promoting SMEs signals a violation of the standards of established theories. The study recommends that the government adopt long-term objectives and strategies for SMEs and take a proactive stance. There is a need to boost research and development (R&D) on the most recent technical advancements in a variety of disciplines for SMEs.